Banana peel and mango kernel-based polymers and their suitability in enhanced oil recovery - Adesina Fadairo; Gbadegesin Adeyemi; Ogunkunle Temitope; Ling Kegang; Rasouli Vamegh; David Enuice; Ilusemiti Temitope; James Ayoo (Journal of Petroleum Exploration and Production Technology, 2021)
Abstract This study reports the extraction and performance evaluation of two bio-derived polymers for enhanced oil recovery applications. The oil displacement processes were conducted using six (6) unconsolidated sandstone core plugs. Reservoir permeability tester was used to simulate real reservoir conditions in order to evaluate the suitability of the formulated biopolymers for oil displacement applications at laboratory conditions. The experimental results indicate the effectiveness of the biopolymer solutions in enhanced oil recovery in terms of their superior incremental oil recoveries after conventional waterflood with percentage oil recovery of 30.9–39.3% for banana peel derived polymer and 40.6–50.8% for mango kernel derived polymer compared to conventional waterflood with percentage recovery of 16.2–32% of the initial oil in place. This work identified the potential suitability and use of bio-derived polymers for enhanced oil recovery applications with emphasis on their biodegradability.